Una nota su metafora e ontologia in Paul Ricœur (Itinera, 2024)
In the last three studies of The rule of metaphor, Ricœur directly develops a referential model for the metaphorical enunciation. Thus, in this contribution, I would like to focus on the ideas that leads Ricœur to speak of a notion of «metaphorical truth», certainly retracing some well-known places on his page (par. I), but also highlighting a point that has not always been adequately emphasised – the reading of metaphors in “configurative” terms (par. II). This last point will serve, in conclusion and as a future avenue of enquiry, to make a small but necessary remark to the ontological development of the ricœurian model of metaphor: the idea that the author is suggesting not only the existence of a reprise at the conceptual level of the creative dynamism proper to metaphorical enunciation, but also the specific determination of this dynamism – its proper “quid” (par. III).
Keywords: Metaphor, Paul Ricœur, Ontology, Configuration